(untitled) (Westport, 2006)
Did you know that the Puritans did not celebrate Christmas? That trick or treating on Halloween began in the late 1930s? That Kwanzaa was created in the mid-sixties by Ron Karenga, a radical Black Nationalist and Black Panther? That Anne Marie Jarvis, the force behind getting Mother's Day, proclaimed a national holiday, later repudiated the holiday for its crass commercialism and strove to undo her handiwork until the day she died? Every holiday has a history, and this set sets out to describe them all. A chronologically organized reference guide to the history of American celebratory days, past, present, and emergent, the books focuse on each holiday's cultural and political significance. It includes major, minor, and bygone holidays, both civic and religious. The work has a distinctive multi-cultural tone, with special emphasis on recent additions to the national holiday pantheon, such as Kwanzaa, Cinco de Mayo, Gay Pride and Passover, among others, in addition to the more traditional Christmas, Thanksgiving, and Veterans Day. New holidays, like The Superbowl and Mardi Gras, are included as well. Each entry tracks the changes in the celebration of the day, its origins, and its wider cultural significance.
Keywords: Các kỳ nghỉ,Holidays; Bách khoa toàn thư,Encyclopedias; Hoa Kỳ,United States